The growth of a large GdPO4 crystal guided by theoretical simulation and the study of its phonon properties. Issue 39 (30th September 2021) - Yang, Zhongmin; Gong, Xinghong; Chen, Yujin; Huang, Jianhua; Lin, Yanfu; Luo, Zundu; Deng, Shuiquan; Huang, Yidong
Abstract : A record size large crystal of GdPO4 was successfully grown aided by theoretical calculations. A new formula was introduced to study the temperature-dependent Raman spectra, which revealed weak phonon–phonon interactions of GdPO4 up to 803 K. Abstract : It has remained a big challenge to grow large crystals of compounds at very anisotropic crystal growth rates. GdPO4 is such an example, which usually grows into a needle-like shape. This work solved this problem by using Li + ions, predicted by first-principles calculations, to adjust the crystal morphology of GdPO4 . Based on the calculated surface energies and the polar properties of the surfaces, we identified two crystal planes, i.e. (−102) and (−111), which can be used to adjust the morphology of the GdPO4 crystal by using extrinsic cations in the flux system. With a predicted Li containing flux system, Li2 O–MoO3 –B2 O3, a large crystal with a record size, 10.0 × 9.0 × 18.2 mm 3, was grown by using the top-seeded solution growth (TSSG) method. Based on the grown large crystal and the polarized Raman measurements, four new Raman bands missing in early studies and other bands were unambiguously assigned. By introducing a new formula, the phonon–phonon interactions were shown to be weak in the temperature range from 83 to 803 K. Our study indicates that the crystal of GdPO4 can be used as a promising laser host material working under relatively high temperature conditions.